Comparison of computed tomography and guided bronchoscopy in the diagnosis of pulmonary nodules: A systematic review and meta-analysis - Wang, Yilin; Liang, Xianhe; Zhang, Haitao; Hao, Jinhua; Wei, Min (Open medicine (Warsaw, Poland), 2025)
To compare the diagnostic effects of computed tomography (CT) and bronchoscopy guided biopsy on pulmonary nodules. "Subject words + free words" were used to search four literature databases including Pubmed, Embase, Cochrane Library, and Web of Science. The subject words were CT, bronchoscope-guided biopsy, pulmonary nodules, and diagnosis. The search is up to August 25, 2023. The retrieved literature was screened, and the literature with duplicate, review, incomplete data or article content and inconsistent with our research was deleted. Revman 5.4 was used for bias analysis of the literatures included in the analysis, and forest map, funnel map, and ROC curve were drawn to compare the accuracy, specificity, and sensitivity of the two diagnostic methods. A total of 2,622 articles were retrieved, and 8 articles were included in the study after screening. Bias analysis and funnel plot showed that eight included articles had higher quality and smaller bias. The sensitivity and specificity of the forest map were both 95% CI, and the sensitivity of CT diagnosis was better than that of bronchoscopy diagnosis, with similar specificity between the two groups. The funnel plot shows some heterogeneity in the literature on pulmonary nodules. The ROC curve shows that CT diagnosis is significantly superior to bronchoscopy diagnosis, with diagnostic accuracy approaching 100%. CT has significant advantages in detecting and diagnosing pulmonary nodules, as it can detect nodules in various parts of the lungs. However, bronchoscopy has significant advantages in diagnosing small pulmonary nodules.